Implications of Good Corporate Governance and Company Size on Profit Management (Study of Lq45 Companies Listed on the Indonesian Stock Exchange) - Syahaq, Fuad Asywadu; Suarni, Agusdiwana; Nurhidayah, Nurhidayah (INVOICE : JURNAL ILMU AKUNTANSI, 2023)
The purpose of this study is to influence good corporate governance and size company on earnings management in LQ45 listed companies Indonesia stock exchange. The type of research used in this study is quantitative. Sample in study This is company LQ45 Which registered on the Indonesia Stock Exchange using purposive sampling method namely sampling technique with certain criteria that produce a number sample 28, Type data Which used form report finance annual. Source data Which used is data secondary. Technique analysis data use assumption classic. Results study show that good corporate governance consists ownership managerial, ownership institutional And committee audits No effect on earnings management, while the independent commissioners and size company influential to management profit, And size company influential significant to management profit.